Phylogeny and Morphology of New Diplonemids from Japan - Tashyreva, Daria; Prokopchuk, Galina; Yabuki, Akinori; Kaur, Binnypreet; Faktorová, Drahomíra; Votýpka, Jan; Kusaka, Chiho; Fujikura, Katsunori; Shiratori, Takashi; Ishida, Ken-Ichiro; Horák, Aleš; Lukeš, Julius (Protist, 2018)
Diplonemids were recently found to be the most species-rich group of marine planktonic protists. Based on phylogenetic analysis of 18S rRNA gene sequences and morphological observations, we report the description of new members of the genus Rhynchopus - R. humris sp. n. and R. serpens sp. n., and the establishment of two new genera - Lacrimia gen. n. and Sulcionema gen. n., represented by L. lanifica sp. n. and S. specki sp. n., respectively. In addition, we describe the organism formerly designated as Diplonema sp. 2 (ATCC 50224) as Flectonema neradi gen. n., sp. n. The newly described diplonemids share a common set of traits. Cells are sac-like but variable in shape and size, highly metabolic, and surrounded by a naked cell membrane, which is supported by a tightly packed corset of microtubules. They carry a single highly reticulated peripheral mitochondrion containing a large amount of mitochondrial DNA, with lamellar cristae. The cytopharyngeal complex and flagellar pocket are contiguous and have separate openings. Two parallel flagella are inserted sub-apically into a pronounced flagellar pocket. Rhynchopus species have their flagella concealed in trophic stages and fully developed in swimming stages, while they permanently protrude in all other known diplonemid species.
Keywords: Sequence Analysis, DNA; Euglenozoa; phylogeny; DNA, Mitochondrial; sekvenční analýza DNA; ultrastructure; RNA, Ribosomal, 18S; RNA ribozomální 18S; flagellates.; description; Phylogeny; Diplonema; fylogeneze; mitochondriální DNA; Japan; Japonsko